2023
DOI: 10.3389/fendo.2023.1083614
|View full text |Cite
|
Sign up to set email alerts
|

The association of apolipoprotein B with chronic kidney disease in the Chinese population

Abstract: BackgroundWhether serum apolipoprotein B (ApoB) is a risk factor for the development of Chronic kidney disease (CKD) has not been fully established in the general population. Therefore, our study evaluated the correlation between serum ApoB level and CKD to look for an alternative approach for CKD prevention and treatment in the general population.MethodsThere were 146,533 participants in this cross-sectional study. 3,325 participants with more than 2 measurements were enrolled in the retrospective longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…In a cross-sectional study involving 146,533 participants, Xu reported that ApoB showed the strongest association with CKD among all lipid parameters. Moreover, elevated serum ApoB values may potentially precede the clinical manifestation of CKD [96]. These insights underscore the importance of monitoring ApoB and other lipid parameters in assessing cardiovascular risk and kidney disease progression in individuals with CKD.…”
Section: Chronic Kidney Disease (Ckd)mentioning
confidence: 93%
“…In a cross-sectional study involving 146,533 participants, Xu reported that ApoB showed the strongest association with CKD among all lipid parameters. Moreover, elevated serum ApoB values may potentially precede the clinical manifestation of CKD [96]. These insights underscore the importance of monitoring ApoB and other lipid parameters in assessing cardiovascular risk and kidney disease progression in individuals with CKD.…”
Section: Chronic Kidney Disease (Ckd)mentioning
confidence: 93%
“…Among polymorphisms in PKCS9 and Apolipoprotein B-100 (ApoB), mutations in ApoB were identified as being associated with greater risk of developing kidney disease among diabetic patients [257]. Indeed, ApoB levels have been correlated with a decline in eGFR [258]. Moreover, patients with familial hypercholesterolemia have reduced eGFR and are at greater risk of CKD [259,260].…”
Section: Protein-induced Kidney Damagementioning
confidence: 99%